High hemoglobin glycation index is associated with increased risk of diabetes: A population-based cohort study in China - Lin, Lu; Wang, Anping; Jia, Xiaomeng; Wang, Haibin; He, Yan; Mu, Yiming; Dou, Jingtao (Frontiers in Endocrinology, 2023)
Purpose: The hemoglobin glycation index (HGI) quantifies the mismatch between glycated hemoglobin A1c and average glycemia among individuals. Currently, it is unknown the potential role of HGI in exhaustively evaluating the progression of glucose metabolism/the risk of developing diabetes mellitus. Therefore, this study aimed to investigate the association between HGI and the risk of incident diabetes. Methods: A total of 7,345 participants aged at least 40 years and without diabetes were divided into three groups according to the tertile of their baseline HGI level and followed for a median of 3.24 years to track new-onset diabetes. Using multivariate Cox regression analyses, we explored the association between the HGI, both categorized and continuous, and incident diabetes. Results: During follow-up, 742 subjects (263 males and 479 females) developed diabetes mellitus. Higher HGI was associated with an increased risk of diabetes, even when adjusted for confounding factors, and every standard deviation increase in HGI was associated with a significant risk increase of 30.6% for diabetes (hazard ratio 1.306, 95% confidence interval 1.232–1.384). Conclusions: Participants with a higher HGI were at a higher risk of future diabetes, irrespective of their glycemic conditions. Consequently, HGI may be employed to identify individuals at high risk for diabetes.